Cervicalgia in patients with migraine - a comorbid nosology or a clinical aspect of central sensitization? - Olga S. Khairutdinova; Enver I. Bogdanov (LLC "MEDIAFORMAT", 2024)
Relevance. The phenomenon of central sensitization occurs when physiological activity in nociceptive pathways increases and leads to abnormal sensitivity; it is defined as "increased sensitivity of nociceptive neurons of the central nervous system to their normal or subthreshold afferent input," according to the definition provided by the International Association for the Study of Pain (IASP). The excitability of spinal cord neurons significantly modifies the gain of the somatosensory system. Chronic pain syndromes, anxiety-depressive disorder, sleep disorders are currently very common in the population, significantly reducing the quality of life of the population; the pathogenesis of these nosologies lies in central sensitization. Objective. To study the clinical manifestations of central sensitization in patients with episodic migraine associated with neck pain or cervicogenic headache. Materials and methods. The longitudinal prospective study included 180 patients, divided into 3 groups: 1) patients with a combination of migraine and cervicogenic headache - 60 people (study group); 2) patients with a combination of migraine and cervicalgia diagnoses - 60 people (control group); 3) patients diagnosed with migraine without complaints of pain and limitation of movements in the cervical spine - 60 people (additional group). Results. In patients with migraine and comorbid cervical headache, more pronounced central sensitization was revealed when compared with comorbid cervicalgia. Myofascial pain syndrome involving the trapezius and temporal muscles can resolve on its own with specific migraine therapy with monoclonal antibodies, however, to relieve tension and soreness in the masseter and inferior oblique muscles, the addition of therapeutic exercises and gentle manual techniques is more effective. Taking into account the identified direct relationships of moderate strength between the number of painful points of exit of the trigeminal nerve, the muscles of the pericranial region involved, as well as the effect of treatment of migraine attacks with monoclonal antibodies, it can be concluded that central sensitization is more pronounced when the masseter and inferior oblique muscles are involved. Conclusions. During examination of patients with migraine with comorbid active cervicalgic factor or even if it is absence, it is necessary to make a thorough examination of the facial and cranioverebral region muscles, even in the absence of patient complaints of pain in the face or neck, and also prescribe specific therapeutic exercises to increase the effectiveness of treatment. In all patients with migraine, regardless of chronicity, it is necessary to assess the intensity of central sensitization for timely and more complete provision of medical care.